2(x+7)=2(3x+11)

Simple and best practice solution for 2(x+7)=2(3x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+7)=2(3x+11) equation:



2(x+7)=2(3x+11)
We move all terms to the left:
2(x+7)-(2(3x+11))=0
We multiply parentheses
2x-(2(3x+11))+14=0
We calculate terms in parentheses: -(2(3x+11)), so:
2(3x+11)
We multiply parentheses
6x+22
Back to the equation:
-(6x+22)
We get rid of parentheses
2x-6x-22+14=0
We add all the numbers together, and all the variables
-4x-8=0
We move all terms containing x to the left, all other terms to the right
-4x=8
x=8/-4
x=-2

See similar equations:

| 16=18y | | -6x+2=-6x+50 | | 20−4x=−12 | | 10^x=1.1 | | 10s-(2s+9)=-3(15-4s) | | 3x^2-7+154=0 | | (2a+8)(a+1)=0 | | 5(-4x+6)=-10 | | 6=7(10d+3)+9 | | 6=7(10d+3 | | 2/5=w+8/4 | | 8=3/2w-4 | | 2x+1-7x=1 | | -16+x=-12 | | x=3-2x+5=10 | | 5x=8-2(2x-6) | | 50=-10000h | | 1x/3-1x/2=12 | | |8e|=24 | | 2x-7+5x=-7 | | 4x+2x-3=7x+8 | | (5u+2)(9+u)=0 | | (X+6)(x-7)=-7 | | -6(3x-2)=-18x-12 | | 8x-7=3x+1 | | 38x+1=-59-21x | | (Y-4)(y+3)(2)+(y+5)(y+3)(4)=(y-4)(y+5)(6) | | 6-6×=-2(x+5) | | 2(3x-3)=-3(2x+6) | | 2/3r=-4/9 | | 3x+5+1=7x+35+8 | | 7n-17=60 |

Equations solver categories